MAHAR MUSAMMA DAN MAHAR MITSIL DALAM PELAKSANAAN PERKAWINAN - Muallim Hasibuan (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2023)
Among the good protections of Islam and its respect for women is that Islam gives them property rights. Because, in the period of ignorance, women became the party whose rights were oppressed and abused in their association. Islam wants to get rid of remnants of the ignorance system regarding women's affairs and their dowry. Mahar is a voluntary gift which is a symbol of a man's sincerity, honesty, and commitment in marrying a woman. Giving a dowry to a prospective wife is mandatory, marriage without mentioning the dowry